The effect of discovery learning with Wamena local content on natural and social sciences learning outcomes and scientific attitudes - Herlince Beri Ledang; I Gede Margunayasa; I Made Citra Wibawa (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study examines the effect of the Discovery Learning model enriched with Wamena local wisdom on natural and social sciences learning outcomes and students’ scientific attitudes in Grade III elementary schools in Wamena. Conventional, non-contextual teaching that is weakly connected to local culture has contributed to low learning outcomes and scientific attitudes, motivating this research. A quantitative approach with a posttest-only quasi-experimental control group design was employed. The sample comprised 35 students in the experimental class, who learned through discovery learning with Wamena local wisdom, and 34 students in the control class, who received conventional instruction. Data was collected using a natural and social sciences achievement test and a scientific attitude questionnaire and analyzed using MANOVA. The results showed that discovery learning with Wamena local wisdom had a significant simultaneous effect on natural and social sciences learning outcomes and scientific attitudes (p < 0.05). The experimental group achieved higher mean scores in natural and social sciences (86.67) than the control group (66.67) and the experimental group students' scientific attitude reached a very high category (102) compared to the control group (92). These findings indicate that the model improves cognitive achievement and fosters critical, contextual scientific attitudes while positioning local culture as a core element of elementary school learning.